FORMULASI DAN ANALISIS MUTU ES KRIM BEKATUL BERAS MERAH (Oryza sativa L) DAN JAMBU KRISTAL (Psidium guajava) SEBAGAI SUMBER MAKANAN TINGGI SERAT DAN VITAMIN C BAGI ANAK SEKOLAH DASAR - Nursalma, Hasna Khairunnisa; Gumilar, Mulus; Judiono, Judiono; Fitria, Mona (Jurnal Gizi dan Dietetik, 2023)
chool-age children are vulnerable to nutritional deficiencies of fiber and vitamin C because they consume less vegetables and fruit. One effort to prevent fiber and vitamin C deficiency is making ice cream products that contain high levels of fiber and vitamin C where the additional ingredients are obtained from brown rice bran and crystal guava. The aim of this research is to determine the effect of red rice bran and crystal guava formulations on the quality of ice cream products including organoleptic properties, fiber content and vitamin C levels. This study used one-factor completely randomized design with 3 formulations of brown rice bran and guava crystals namely F1 (15%:85%), F2 (25%:75%) and F3 (35%:65%). The research method used the hedonic test to determine the organoleptic properties, enzymatic gravimetry for the fiber test and iodimetri titration for the vitamin C test. Formula F1 (15%:85%) was the best formula that contains 5.19 g of fiber and 38.4 mg of vitamin C, thus fullfilled a daily requirements of fiber and vitamin C for elementary school children approximately 20% and 80% in one serving (80 g). The Kruskall Wallis test revealed that there was an effect of different formulations of red rice bran and crystal guava ice cream on the color, taste and overall of the ice cream (p<0.05). The production cost of F1 ice cream is IDR 3,000/80 g. Red rice bran and crystal guava ice cream products should be subjected macronutrient analysis in the laboratory using proximate testing.